2021
DOI: 10.1039/d0en00944j
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent plastic nanoparticles to track their interaction and fate in physiological environments

Abstract: This work aims to establish a production and characterization protocol for fluorescent plastic nanoparticles of poly(ethylene terephthalate) (PET), polypropylene (PP), and polystyrene (PS) that can be tracked in biological environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Another advantage of the proposed method consists in achieving a polydisperse size distribution that makes easier separation by size for further studies of interaction with marine organisms. The observed size heterogeneity could be similar to that present in the real nanoplastics gathered in the marine environment [28,46], which are produced by the degradation of primary and secondary microplastics with a ball milling-like process where small hard sand granules play the role of zirconia balls in the proposed laboratory experiments. However, if for a specific experiment, a size fraction of NPs is required, the aqueous dispersion can be subject to centrifugation and filtration in order to collect, for example, only a close nanometric fraction.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Another advantage of the proposed method consists in achieving a polydisperse size distribution that makes easier separation by size for further studies of interaction with marine organisms. The observed size heterogeneity could be similar to that present in the real nanoplastics gathered in the marine environment [28,46], which are produced by the degradation of primary and secondary microplastics with a ball milling-like process where small hard sand granules play the role of zirconia balls in the proposed laboratory experiments. However, if for a specific experiment, a size fraction of NPs is required, the aqueous dispersion can be subject to centrifugation and filtration in order to collect, for example, only a close nanometric fraction.…”
Section: Discussionsupporting
confidence: 67%
“…Even if the nanometric sizes achieved by the three procedures are comparable, Procedure C is more efficient, with the highest yield of nanometric fraction below 1 µm, equal to 36.4% by volume, achieved in the lowest time. The milling time of about 36 min is very low if compared to the 3 h reported for PET nanoplastics with a different ball mill but with the same ZrO 2 ball diameter [46]. The effectiveness of ball milling with hard small spheres can be considered a process very close to what can occur on sea shores, where hard sand granules hit meso-and microplastics at low rates but for a time incommensurably longer.…”
Section: Optimization Of Wet Ball Milling For Producing Pet Nanoplasticsmentioning
confidence: 81%
See 2 more Smart Citations
“…A recent study suggested that the preparation of PPNPs as model plastic nanomaterials and a subsequent labeling technique were important to improve toxicological and biodistribution studies. PPNPs were produced with high yield (>84%) by nonsolvent-induced phase separation (NIPS), which is a unique method that is neither a bottom-up method, such as polymerization, nor a top-down method, such as ball milling or cryomilling. , The physical and chemical properties of the as-prepared PPNPs were fully characterized using scanning electron microscopy (SEM), dynamic light scattering, Fourier-transform infrared (FT-IR) spectroscopy, and differential scanning calorimetry (DSC) and successfully fluorescently labeled for visualization of their biofate in zebrafish embryos (ZFEs) as an animal model.…”
Section: Introductionmentioning
confidence: 99%